2016
DOI: 10.1136/neurintsurg-2016-012619
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of intracranial aneurysms in patients with aortic dissection or aneurysm: feasibility of extended aorta CT angiography with involvement of intracranial arteries

Abstract: With a high prevalence of IAs in patients with ADs or AAs, extended aorta CTA could be used to evaluate aorta disease and IA in a single session. However, further prospective studies are needed to prove efficacy and safety of the extended aorta CTA protocol in patients with AAs or ADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Given high prevalence of concomitant aortopathy (ie, 40–70%) in patients with BAV, the more frequent occurrence of IAs in BAV cohort might be only a marker of a more generalised arteriopathy/aortopathy rather than an indicator of BAV morphology itself. Of note, several retrospective studies revealed high prevalence (ie, 35/158 (22%)) of IAs in patients presenting with thoracic aortic aneurysms and dissections 5. In accordance with this finding, a total of 13–17% patients diagnosed with thoracic aortic aneurysms had concomitant IAs,6 while most of the patients with BAV and concomitant IA had a dilated thoracic aorta (ie, 5/6 (83%)) 7.…”
supporting
confidence: 56%
“…Given high prevalence of concomitant aortopathy (ie, 40–70%) in patients with BAV, the more frequent occurrence of IAs in BAV cohort might be only a marker of a more generalised arteriopathy/aortopathy rather than an indicator of BAV morphology itself. Of note, several retrospective studies revealed high prevalence (ie, 35/158 (22%)) of IAs in patients presenting with thoracic aortic aneurysms and dissections 5. In accordance with this finding, a total of 13–17% patients diagnosed with thoracic aortic aneurysms had concomitant IAs,6 while most of the patients with BAV and concomitant IA had a dilated thoracic aorta (ie, 5/6 (83%)) 7.…”
supporting
confidence: 56%
“…Several single-center case series have reported a prevalence of IA and AAA to range from 2.2 to 20.3%. [10][11][12][13][14] Most recently, a population-based study, by Wang et al demonstrated a significant increase in the rate of IA among surgical aortic aneurysm patients compared with the general population. 17 The study however, includes all aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Estimates of the coprevalence of IA and AAA vary widely from 2.2 to 20.3%. [10][11][12][13][14] Effective surgical and endovascular treatments exist for unruptured intracranial and AAAs; therefore, screening high-risk individuals could significantly reduce mortality related to both types of aneurysmal rupture. In a previous prospective study, 15 we observed a 12% prevalence of previously undiagnosed AAA in patients who presented with aneurysmal subarachnoid hemorrhage.…”
mentioning
confidence: 99%
“…It is known from current epidemiological studies that intracranial aneurysms (IA) may have a direct link to other aneurysms in the body, particularly to abdominal aortic aneurysms (AAA) and thoracic aortic aneurysms (TAA). [1][2][3][4][5][6][7][8][9][10][11][12][13] There are incidences of co-occurrence and a pattern of inheritance and familial clustering. 14 There may be common genetic and pathological determinants for the development of these aneurysmal types.…”
Section: Introductionmentioning
confidence: 99%